Han contribuido los fondos del segundo pilar de la PAC 2007-2013 a la creación de empleo en la asturias rural? Un enfoque de econometria espacial con datos de corte transversal; Have the funds of the second pillar of the Cap 2007-2013 contributed to the creation of employment in rural asturias? A spatial econometric approach with cross-sectional data - Óscar Luis Alonso Cienfuegos (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– The contents of the present work focus on contrasting the possible contribution of the funds from the second pillar of the Common Agricultural Policy (CAP) to improving the evolution of one of the economic variables that is usually included as an objective to be achieved by rural development plans, the creation of employment. The economic study data distributed in space must necessarily take account spatial econometric techniques, considering the possible effects of autocorrelation and spatial heterogeneity, which if overlooked may cause the results of the econometric analysis are invalid, losing the statistical properties required.
Keywords: C21; O18; R11; R58; 330; spatial econometrics; rural development; exploratory analysis of spatial data; confirmatory analysis; changing regressions